(untitled) (The Agriculturists, 2016)
Soil organic matter, nitrogen (N), phosphorus (P) and potassium (K) nutrition of rice-maize cropping systems are important for sustaining crop productivity and food security. An experiment was conducted to determine the effects of tillage practices and residue retention on soil chemical properties in rice-maize cropping system. Conventional tillage, single pass wet tillage in rice (rotated with zero tillage in maize), bed planting (unpuddled rice transplanting) and strip tillage (unpuddled rice transplanting) in vertical plots and residue retention (0, 50 and 100%) in horizontal plot were tested for three consecutive years (2009-12). Rice was grown as transplanted irrigated crop and maize as upland crop. After third crop, strip tillage increased soil organic matter compared to bed and zero tillage at 07.5 cm soil depth. After three years, retention of crop residues, irrespective of tillage treatments, increased soil organic matter (SOM) at 7.515.0 cm soil depth. Tillage practices (puddled or unpudled) showed no significant changes in SOM. Neither tillage nor residue management had any significant effect on soil pH, total nitrogen, available phosphorus and exchangeable potassium. DOI: http://dx.doi.org/10.3329/agric.v13i2.26589 The Agriculturists 2015; 13(2) 62-73